Impact of hepatitis E virus seropositivity on chronic liver disease in cancer patients with hepatitis C virus infection. Issue 11 (6th January 2015) - Kyvernitakis, Andreas; Taremi, Mahnaz; Blechacz, Boris; Hwang, Jessica; Jiang, Ying; Mahale, Parag; Torres, Harrys A.
Abstract : Aim: Immunocompromised patients can develop chronic hepatitis E virus (HEV) infection and progress to cirrhosis. Hepatitis C virus (HCV)‐infected cancer patients who have received chemotherapeutic agents experience accelerated liver fibrosis progression. Our aim was to investigate the prevalence and impact of HEV seropositivity on liver‐related outcomes in HCV‐infected cancer patients. Methods: As part of a prospective study of HCV‐infected cancer patients conducted at our center, we investigate the characteristics associated with progression of their liver disease. Results: Of the 115 patients tested, 13 (11%) were positive for HEV immunoglobulin G. HEV seropositivity was associated with advanced age ( P  = 0.004), race ( P  = 0.02), place of birth outside the USA ( P  = 0.021), cirrhosis ( P  = 0.027), history of reused needles/syringes during massive vaccination campaigns ( P  = 0.015) and coronary artery disease ( P  = 0.039). Overall, 47 (41%) of the patients had cirrhosis. Factors independently associated with cirrhosis were male sex (odds ratio [OR], 2.8; P  = 0.028) and HEV seropositivity (OR, 4.1; P  = 0.032). Conclusion: HEV seropositivity is present in 11% of HCV‐infected cancer patients and seems to be associated with cirrhosis. Our results suggest that HEV screening should be implemented in HCV‐infected patients with cancer.